2020
DOI: 10.1002/jso.25839
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant chemotherapy on surgical and pathological results of gastric cancer patients: A case‐control study

Abstract: Background and Objective Neoadjuvant chemotherapy (NACT) followed by radical surgery represents a treatment option for patients with advanced gastric cancer (GC). This case‐control study aimed to evaluate the clinicopathological characteristics and surgical outcomes of GC patients who received NACT, and its impact on survival. Methods We retrospectively reviewed all patients with GC who underwent gastrectomy. A total of 45 cases with NACT were matched with consecutive 45 patients who underwent upfront gastrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 31 publications
4
41
1
Order By: Relevance
“…This can be due to the suboptimal reliability of clinical staging of gastric cancer, with an overall CT scan accuracy for T staging ranging from 43% to 82% 5 and an overall EUS accuracy for T and N staging of 46.2% and 66.7%, respectively. In the studies reporting specific clinical stages, 6,10,36 72%–93% of patients had cT3/4 and 55‐80% had cN + . However, few studies reported the distribution of the patients between cStage II and cStage III 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to the suboptimal reliability of clinical staging of gastric cancer, with an overall CT scan accuracy for T staging ranging from 43% to 82% 5 and an overall EUS accuracy for T and N staging of 46.2% and 66.7%, respectively. In the studies reporting specific clinical stages, 6,10,36 72%–93% of patients had cT3/4 and 55‐80% had cN + . However, few studies reported the distribution of the patients between cStage II and cStage III 10 …”
Section: Discussionmentioning
confidence: 99%
“…Although surgery remains the only curative treatment for gastric cancer in the last decades, several multimodal approaches have been developed to improve long‐term survival. Among them, perioperative chemotherapy (PC) has gained growing attention due to its potential to improve R0 resection and survival rates 5,6 . PC is administered both before, so‐called neoadjuvant chemotherapy (NACT), and after curative surgery so‐called adjuvant chemotherapy (ACT).…”
Section: Introductionmentioning
confidence: 99%
“…In the ERAS guidelines for gastric cancer resection, the strength of recommendation for each ERAS measure is buttressed by high levels of evidence; however, NAC has never been included in the ERAS protocol and some studies purposefully excluded patients who received NAC [17,18]. A large body of evidence con rms that NAC can not only effectively downgrade advanced gastric cancer after a patient undergoes a palliative operation to achieve R0 resection, but also signi cantly improves long-term survival by reducing the recurrence of cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In the ERAS guidelines for gastric cancer resection, the strength of recommendation for each ERAS measure is buttressed by high levels of evidence; however, NAC has never been included in the ERAS protocol and some studies purposefully excluded patients who received NAC [17,18]. A large body of evidence con rms that NAC can not only effectively downgrade advanced gastric cancer after a patient undergoes a palliative operation to achieve R0 resection, but also signi cantly improves long-term survival by reducing the recurrence of cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%